2003
DOI: 10.1159/000070851
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Correlates of the Progression Rate of the Cognitive Decline in Probable Alzheimer’s Disease

Abstract: Objective: To evaluate the possible relation between the rate of cognitive deterioration in patients with probable Alzheimer’s disease (AD) and the distribution pattern of neural dysfunction. Methods: The regional cerebral blood flow (rCBF) was measured in rapidly and slowly progressing groups of AD patients using single-photon emission computed tomography and was compared between the groups. While controlling for demographic and clinical factors that could be associated with the stage and prognosis of the ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 37 publications
0
37
1
1
Order By: Relevance
“…For greater levels of conflict, such as those experienced during both the preparation and decision phase of the task after the red cue, the cognitive demands might have exceeded the MCI's compensatory reserve, thus yielding a next to null load-related response in dlPFC. The weak response of dlPFC to the load of the task observed in MCI may reflect frontal lobe neural degeneration (Encinas et al 2003;Nagahama et al 2003) in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…For greater levels of conflict, such as those experienced during both the preparation and decision phase of the task after the red cue, the cognitive demands might have exceeded the MCI's compensatory reserve, thus yielding a next to null load-related response in dlPFC. The weak response of dlPFC to the load of the task observed in MCI may reflect frontal lobe neural degeneration (Encinas et al 2003;Nagahama et al 2003) in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient cerebral blood flow is also vital for optimal brain function, with several studies indicating that there is a decrease in cerebral blood flow (CBF) in patients with dementia [71,87]. Brain imaging techniques, such as 'functional magnetic resonance imaging' (fMRI) and 'trans-cranial Doppler ultrasound' (TCD) has shown that there is a correlation between CBF and cognitive function Fig.…”
Section: Cerebrovascular Effects Of Flavonoidsmentioning
confidence: 99%
“…Indeed, new hippocampal cells are clustered near blood vessels, proliferate in response to vascular growth factors and may influence memory [49]. Efficient cerebral blood flow (CBF) is vital for optimal brain function, with several studies indicating that there is a decrease in CBF in patients with dementia [48,52]. Brain imaging techniques, such as 'functional magnetic resonance imaging' (fMRI) and 'trans-cranial Doppler ultrasound' (TCD) has shown that there is a correlation between CBF and cognitive function in humans [52].…”
Section: Modulation Of Memory and Learningmentioning
confidence: 99%